SUKSESI BISNIS KELUARGA: SINKRONISASI NILAI TRADISI JAWA DAN PRINSIP KEADILAN ISLAM DALAM KELANGSUNGAN USAHA KECIL: Family Business Succession: Synchronizing Javanese Traditional Values and Islamic Principles of Justice in the Sustainability of Small Enterprises - Agapito Barros (tesco publisher, 2025)
The continuity of family businesses faces crucial challenges during intergenerational succession, where failure rates often increase sharply from the first to the second and subsequent generations. This study aims to explore the mechanisms of value transfer in family business succession in the Micro, Small, and Medium Enterprises (MSMEs) sector, particularly in the batik industry center of Central Java. The main focus of the study is how business actors synchronize Javanese traditional values ​​(local wisdom) with the Islamic principle of justice (Al-'Adl) to ensure business sustainability. This research uses a qualitative method with a phenomenological case study approach. Data collection was conducted through in-depth interviews, participant observation, and documentation in five batik business families that have survived for more than two generations. The results show that successful succession depends not only on the transfer of capital assets but also on the transmission of